Autopsy Findings in Three Patients with von Willebrand Disease Type IIB and Type III: Presence of Atherosclerotic Lesions without Occlusive Arterial Thrombi - Federici, A B; Mannucci, P M; Fogato, E; Ghidoni, P; Matturri, L (Thrombosis and Haemostasis, 1993)
It has been reported that pigs with severe von Willebrand disease (vWd) are protected from spontaneous and diet-induced atherosclerosis, but there are very few studies in human patients. Autopsies were carried out on three patients with vWd (one case with the type IIB variant and two cases with type III, a variant similar to that protecting pigs from atherosclerosis), aged 73, 44 and 52 years at the time of death. Hemorrhagic diathesis was an important cause of death for these patients. Atherosclerosis lesions were found in all patients, though of different extent and localization: severe lesions in all vascular areas in the patient with type IIB, few and slighter in all areas in the two patients with type III, except that in one of them there were moderately severe lesions in the coronary arteries. There was no clinical or pathologic evidence of thrombosis in the coronary arteries or other arteries. These data indicate that severe vWd did not protect completely against the development of atherosclerosis, although it is possible that intensive lifelong treatment with plasma concentrates had a modifying influence in these patients.